Mothering, Substance Use Disorders and Intergenerational Trauma Transmission: An Attachment-Based Perspective - Meulewaeter, Florien; De Pauw, Sarah S. W.; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2019)
Background: A growing body of research underlines that interpersonal trauma in childhood leads to heightened susceptibility for substance use disorders (SUDs) in later life. Little research has been conducted on parenting experiences of mothers in recovery from substance use, taking into account their own upbringing as a child and the potential aftermath of interpersonal childhood trauma. Methods: Through in-depth qualitative interviews, 23 mothers with SUDs reflected on parenting experiences and parent-child bonding, related to both their children and parents. Interviews were transcribed verbatim and data were analyzed adopting thematic analysis. Results: Throughout the narratives, consequences of trauma on mothers’ sense of self and its subsequent impact on parenting arose as salient themes. Five latent mechanisms of intergenerational trauma transmission were identified: 1) early interpersonal childhood trauma experiences in mothers; 2) trauma as a precursor of substance use; 3) substance use as a (self-fooling) enabler of parental functioning; 4) continued substance use impacting parental functioning; and 5) dysfunctional parental functioning and its relational impact upon offspring. Discussion: Findings suggest disruptive attachment can increase the vulnerability for SUDs on the one hand, but can be an expression of underlying trauma on the other, hence serving as a covert mechanism by which trauma can be transmitted across generations. Results indicate the need for preventive, attachment-based and trauma-sensitive interventions targeted at disruptive intergenerational patterns.